E-Training Of The Cybersecurity For The Senior High School Teachers - Syahtriatna Djusar; Elvira Asril; Muhamad Sadar (Universitas Negeri Padang Press, Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi, Fakultas Ilmu Keolahragaan, Univeristas Negeri Padang., 2020)
Obstacles In Conventional Learning Or Face-To-Face Forcing Some Teachers To Switch To Using The Online Learning Process. The Development of the Covid-19 Virus Outbreak Has Changed the Way of Learning Nationally in Indonesia, including High Schools in Riau Province. Teachers Are Asked To Implement Online Learning Processes Using A Variety Of Available Applications, Either Applications That Are Available For Free Or Applications That Are Paid For. The Use of Applications by Some Teachers, Accompanied by the Development of Information Systems Security Issues, Which Causes Some Teachers to Be Doubtful and Fear of Using Available Applications. The Online Training is conducted in the form of counseling and workshops for participants who are teachers in several high schools / equivalent in Riau Province. Online Training That Has Been Held Has Been Giving Benefits To Teachers In Knowing And Sorting Correct News And Lying News, And An Increased Ability And Skills Of Teachers Regarding Information Systems Security.